Fractional calculus and itÂ´s applications to the non-homogeneous gauss’ equations - Nishimoto, K. (Rev. Téc. Fac. Ing. Univ. Zulia)
Some other many papers on fractional calculus have been reported by the author. In this paper, where firstly, we will show a table of fractional differintegrations of elementary functions which is obtained obeying the definition of author. Next we will show an application of our fractional calculus to the non-homogeneous Gauss’ equation which is a differential equation of Fuchs type.